2018
DOI: 10.19166/med.v6i3.1147
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Histopatologik dan Imunofenotipik Kanker Payudara di Rumah Sakit Cipto Mangunkusumo Jakarta, Indonesia

Abstract: <p>Introduction: Breast cancer can be classified into luminal A, luminal B, Her2+, dan basal-like molecular subtype according to genetic profile and immunophenotype. The aim of this study is to assess histopathologic and immunophenotype characteristics of breast cancer in Cipto Mangunkusumo Hospital Jakarta, Indonesia.<br />Material and methods: This study is a cross-sectional retrospective study. The sample was 2632 breast cancer case in Department of Anatomical Pathology Cipto Mangunkusumo Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
0
0
4
Order By: Relevance
“…Cipto Mangunkusumo who showed that based on the histopathological grade, patients with moderate grade (grade 2) were found more often, namely 1053 cases (40%) compared to patients with low and high malignancy degrees. [31] The results of this study are also in line with research conducted at RSUD Dr. Moewardi Surakarta which shows that of the threegrading histopathology, each of them had negative estrogen receptor expression which was mostly found compared to positive estrogen receptor expression. [30] According to the researcher's assumptions, patients in RSUD.…”
Section: Resultssupporting
confidence: 86%
“…Cipto Mangunkusumo who showed that based on the histopathological grade, patients with moderate grade (grade 2) were found more often, namely 1053 cases (40%) compared to patients with low and high malignancy degrees. [31] The results of this study are also in line with research conducted at RSUD Dr. Moewardi Surakarta which shows that of the threegrading histopathology, each of them had negative estrogen receptor expression which was mostly found compared to positive estrogen receptor expression. [30] According to the researcher's assumptions, patients in RSUD.…”
Section: Resultssupporting
confidence: 86%
“…Di Rumah Sakit Cipto Mangunkusoma Jakarta, pada tahun 2015 menunjukkan paling banyak adalah tipe luminal B (43,9%), diikuti HER2 (14,6%), luminal A (14,0%), dan basal-like (11,3%). 12 Sedangkan di Rumah Sakit Sanglah Denpasar, pada tahun 2012 menunjukkan terbanyak adalah tipe luminal A. Subtipe luminal A/ subtipe basal-like/triple negative (37,4%), diikuti HER-2 positif (15,6%) dan paling sedikit luminal B (9,5%). 13 Suptipe molekuler kanker payudara bisa jadi berbeda bahkan pada sesama orang Asia.…”
Section: Pendahuluanunclassified
“…23 Tipe histopatologi terbanyak di RS Madiun adalah karsinoma duktal invasif, dan hal yang sama juga ditemukan di RS Arifin Ahmad, Riau; RSCM, Jakarta; dan RS Kariadi, Semarang. 12,18,24 Secara global subtipe histologi ini adalah yang paling umum yaitu sampai 75% dari semua karsinoma invasif. Tipe ini memiliki cakupan morfologi yang bervariasi begitu juga perilaku klinis.…”
Section: Pembahasanunclassified
See 2 more Smart Citations